KEWENANGAN JAKSA PENUNTUT UMUM DALAM UPAYA HUKUM PENINJAUAN KEMBALI - Damayanti, Fitria Indah; Soeskandi, Hari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
A review by the prosecutor in a criminal case is a paradox that occurs in the criminal law system, where the legal practice is contrary to the values and legal norms as regulated in the Criminal Procedure Code. However, in practice, judicial review is often carried out by prosecutors on the grounds that there is court jurisprudence that decides the case, as a result the law does not reflect justice and certainty and even tends to conflict with the legal interests of the convict and his heirs. The research method uses a normative juridical method with an emphasis on literature study. analysis is carried out on legal norms, both the law in statutory regulations and the law in court decisions). The conclusions drawn are that the submission for judicial review is solely for the benefit of the convict and his heirs, the law and the constitution do not authorize the prosecutor to conduct a review, that the review carried out by the prosecutor is not a legal discovery but only an interpretation of the law, the submission of a judicial review by the prosecutor is a form of court error which indicates that there is a logical fallacy in the practice of criminal law in Indonesia. Suggestions for developing the theme of this paper is that the Supreme Court should issue a circular containing prohibitions and restrictions for prosecutors to apply for a review or conduct a judicial review and annulment of cases that are submitted for review by the prosecutor